Interaction ou inter-actions? Deux conceptions de la notion d'interaction - Grossen Peretti, Michèle (My University, 2018)
This article aims at discussing two main definitions of the concept of interaction: the first one assumes that an interaction is the sum of individual actions (inter-actions) while the second one assumes that interaction is an inseparable unit of analysis. They constitute what can be called a factorial vs. dialogical conception of interaction. After having presented these two conceptions and shown some gaps between theoretical assumptions and methodological practices, we discuss what methodological consequences for research a dialogical conception of interaction may have, provide the example of a study which tried to take these consequences into account, and conclude with some challenges that have to be faced in future research.